Bond of deformed steel reinforcement in lightweight foamed concrete. (7th March 2017) - de Villiers, Johannes P.; van Zijl, Gideon P.A.G.; van Rooyen, Algurnon S.
Abstract : Low weight and thermal insulating properties make lightweight foamed concrete (LWFC) an attractive substitute for normal‐weight concrete (NWC). The unfamiliarity and paucity of design guidance challenge the structural use of LWFC. One concern is the bond of steel reinforcement in LWFC. This paper presents the results of pull‐out bond tests and beam‐end bond tests. The parameters were a reference NWC and LWFC with densities of 1, 200, 1, 400, and 1, 600 kg/m 3 and rebar diameters of 10, 12, and 20 mm with embedded lengths of 3, 4, and 5 bar diameters. All concretes were characterized in terms of strength, stiffness, and fracture energy. Clear differences in bond resistance were found from the two tests. The bond in LWFC is lower than that in NWC. The results suggest that the development of LWFC materials to increase fracture energy has the potential to increase the bond.